Medication Beliefs, HIV-Related Stigmatization, and Adherence to Antiretroviral Therapy: An Examination of Alternative Models. Issue 1 (2nd January 2021) - Mitzel, Luke D.; Foley, Jacklyn D.; Sweeney, Shannon M.; Park, Aesoon; Vanable, Peter A.
Abstract: HIV-related stigma and beliefs about medication necessity and concerns have separately demonstrated significant associations with antiretroviral adherence in people with HIV. However, no work has examined both of these associations in the same model. Based on the necessity-concerns framework, this study examined four alternative models of relationships among HIV-related stigma, medication beliefs, and adherence. Cross-sectional analyses were used to test the four alternative models to best depict associations among HIV-related stigma, medication beliefs, and medication adherence. Models tested included two indirect effects models, an interaction model, and a simple predictors model with no interaction or indirect effects. The outcome variable was HIV medication adherence, and model fit was determined by variance accounted for, Akaike information criterion (AIC), and Bayesian information criterion (BIC) values. An interaction model between internalized stigma and medication concerns accounted for the most variance in adherence. There was also a significant indirect effect of internalized stigma on adherence via medication concerns. Medication concerns are a promising target for interventions focusing on increasing adherence among people with HIV.